2023
DOI: 10.1021/acscatal.3c03538
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the α-Ketoamide Inhibition Mechanism: Revealing the Critical Role of the Electrostatic Reorganization Effect of Asp17 in the Active Site of the 20S Proteasome

Jiao Zhou,
Xiaohong Sang,
Juan Wang
et al.

Abstract: The 20S proteasome is an attractive drug target for the development of anticancer agents because it plays an important role in cellular protein degradation. It has a threonine residue that can act as a nucleophile to attack inhibitors with an electrophilic warhead, forming a covalent adduct. Fundamental understanding of the reaction mechanism between covalent inhibitors and the proteasome may assist the design and refinement of compounds with the desired activity. In this study, we investigated the covalent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Extensive experiments and theories have shown that externally applied electric fields or internal electric fields intrinsically present in certain catalysts can be used to effectively control chemical activity and selectivity. Specifically, the significant role of electric fields has been extensively researched in both natural and synthetic enzymes. Protonation of His180, adding a positive charge to the imidazole ring of its side chain, notably alters the electrostatic environment in which the PCET reaction takes place. We examined the electrostatic impact of the positively charged HIP180 by using Mulliken charges from QM/MM calculations to assess the interaction energy between His180’s charged side chain and the PCET reaction complex, including FADH – , FMN, Glu142, and the bridging water molecules.…”
mentioning
confidence: 99%
“…Extensive experiments and theories have shown that externally applied electric fields or internal electric fields intrinsically present in certain catalysts can be used to effectively control chemical activity and selectivity. Specifically, the significant role of electric fields has been extensively researched in both natural and synthetic enzymes. Protonation of His180, adding a positive charge to the imidazole ring of its side chain, notably alters the electrostatic environment in which the PCET reaction takes place. We examined the electrostatic impact of the positively charged HIP180 by using Mulliken charges from QM/MM calculations to assess the interaction energy between His180’s charged side chain and the PCET reaction complex, including FADH – , FMN, Glu142, and the bridging water molecules.…”
mentioning
confidence: 99%